Dissolution of marriage on the ground of cruelty: A comparative overview of Fasakh and irretrievable breakdown of marriage (IBM) principles - Md Hashim, Noraini; Abas, Afridah; Abdul Hak, Nora (2010)
In Islam, if a husband treated his wife with cruelty either physically or mentally, she has the right to apply to the court for marriage to be dissolved, on the ground of fasakh. The practice in Malaysia, the Shariah Court will ask the wife to provide sufficient evidence to prove her claim, failure of which the application for fasakh will be set aside. In some cases, a Shariah Court demanded on higher standard of proving the act of cruelty by the husband. For example, a Shariah Court had insisted on the requirement of two male witnesses, who saw the act of beating the wife. This caused difficulty to the wife as it would not be easy for her to fulfill this requirement. Whilst, under section 54 (1) (b) of the Law Reform (Marriage & Divorce) Act 1976) (herein after referred to as LRA 1976), stated that the plaintiff may petition for divorce on the ground that the respondent has behaved in such a way and thus, the plaintiff cannot be reasonably be expected to live with the respondent. The act of cruelty of the respondent either physically or mentally is more than adequate to the term behavior as stated under the present divorce law. In the case of irretrievable breakdown of marriage (herein after referred to as IBM) both objective and subjective tests have been used by the court to decide whether or not the plaintiff can reasonably be expected to live with the respondent in consequence of the respondent’s behavior including cruelty. If it is proven, then the application for divorce will be granted by the court. The paper will examine the above issues relating the methods of proof and evidentiary requirement in cruelty cases. Relevant legal provisions as provided under Malaysian laws i.e., the LRA 1976 and the Islamic Family Law Act/Enactments and the practice of the Malaysian courts deliberating this issue will be the focus of the paper. Decisions of the Shariah and Civil Courts on cruelty in divorce cases will be analysed to study the practice in Malaysia highlighting the problems and restrictions. The paper proposes some solution and suggestions.